Human resource crises in Chinese enterprises - Gao, Junhong; Alas, Ruth (Business: Theory and Practice, 2010)
This research paper provides a HR crisis management reference for Chinese organisations. The aims of this paper are to discover and describe HR crises and management situations in Chinese organisations. The research questions are as follows: 1) – How did the crisis happen? 2) – How did the company handle the crisis? 3) – What result came from the crisis? In this paper, exploratory and descriptive approaches were used to complete the survey. The qualitative method (interview) was used in this study since it enables one to gain a deeper knowledge and understanding of the detailed information. The interviews included both open and closed-ended questions. The method used to analyse the primary data was ordinal. The results indicate that HR crises are caused by various factors – both internal and external. The internal reasons are enterprise’s managerial systems change, employees’ dissatisfaction, managerial inappropriateness, and enterprise development. The external reasons are inner-industry HR competition, local government policy change, and accident. Due to the limited number of samples, it is necessary to expand the study and conduct more empirical research so as to draw more comprehensive conclusions. The conclusions and implications should be considered by managers in Chinese enterprises, especially HR managers and crisis managers, when detecting, distinguishing and determining a crisis.